Caterpillar: a service brand for customer peace of mind - Goffin, Keith (Henry Stewart Talks, 2017)
The case study describes the construction equipment company Caterpillar’s approach to customer service, in particular its commitment to meeting customer’s technical and emotional needs before they are aware of having them.